Chemical studies and pharmacological activities of species belonging to the Byrsonima genus: an integrative review (Research, Society and Development, 2022)
The present study aimed to integrate the results of different chemical and pharmacological studies of species belonging to the genus Byrsonima. The search for articles was performed through three databases (SCOPUS, MEDLINE, PUBMED), where the strings “Byrsonima AND medicine pharmaceutical” were used in the last 5 years. In addition, it was researched in Capes journals, without period limitation. Sixty-five articles were found in which titles and abstracts were read. In the next step, 30 articles were read in full, excluding those that had no relation to the topic. The following information was collected from the articles: chemical characterization, isolated substances, results of pharmacological studies. In the end, 24 articles could be included in this review and dealt with chemical and/or pharmacological studies. Antioxidant activity was reported for different species of Byrsonima, using different methods of analysis. Also, they showed promise for anti-inflammatory and antinociceptive activities. Antioxidant, anti-inflammatory, and analgesic activities of species belonging to this genus have been related to phenolic compounds, especially flavonoids. In addition to these activities, species of Byrsonima seem to be promising as gastroprotective, antituberculosis, and antiparasitic. The studies that evaluated the toxicity are scarce, being included only 2 articles that demonstrated that the different species have cytotoxic potential. This way, it’s possible to identify and synthesize the activities present in the species of the genus, in order to facilitate future studies.